PRODUCTION OF POLYCLONAL ANTIBODIES AGAINST INDIAN PAPER WASP ROPALIDIA MARGINATA VENOM TOXINS AND THEIR EFFICACY IN THE REVERSAL OF TOXIC EFFECTS - UPADHYAY, RAVI KANT; SHARMA, SIMRAN (International Journal of Pharmacy and Pharmaceutical Sciences, 2024)
Objective: In this study, albino mice were injected with a sub-lethal dosage of purified wasp Ropalidia Marginata venom toxins to assess the effectiveness of polyclonal anti-venom antibodies. Methods: To neutralize the toxic effects, polyclonal antibodies were generated by immunizing albino mice. The antibody underwent partial purification using ammonium sulphate treatment and octanoic acid precipitation. To detect the presence of antibodies in the antiserum, an immunodouble diffusion test was conducted using Ouchterlony's method (1962). This involved allowing both antigens and antibodies to diffuse radially towards each other from their respective wells. When they reached an equivalence zone, a precipitation complex of antigen and antibody became visible as a concentric band, indicating the development of the combination. To quantitatively determine the amount of antibodies in the antiserum, the equivalency zone approach was used. Results: Experimental mice were injected with a combination containing 400, 800, and 1200 µg of pure antibody, which had been treated serum biomolecules, including metabolic enzymes, completely reversed in the experimental with 40% of the LD50 of wasp venom the elevated serum parameters were glucose, pyruvic acid, lipid, protein and free amino acid, reached to normal (100%) in the treated with 40% of LD50 of the venom and polyclonal treated after 6 h of administration. Anti-serum treatment also successfully normalized the alteration in serum enzyme just after 4h. Similarly, anti-serum treatment also successfully normalized the alteration in serum enzyme just after 4h treated with 40% of LD50 of the venom. Serum ACP content was obtained as 125.35% after 40% of LD50 venom injection, which was get normalized up to 102.81% after 4 h of the anti-venom treatment. Serum ALP content of 114.8% elevation was reversed back to 102.40% after anti-venom treatment. The GPT level significantly reversed up to 102.5%, while it was 130% in the venom-treated mice. A complete reversal was obtained in GPT level, which was obtained as 104.54% in the venom-treated animal. Similarly, LDH which was elevated up to 112.45 % in venom-injected mice was successfully reversed up to 100.25% after anti-venom treatment. Similarly, Ache concentration was fully recovered after anti-venom treatment 6 h, all animals (group B-E) that had received 40% of the LD50 of venom treated with pure antiserum. Conclusion: The venom-injected group showed a complete restoration of serum protein, free amino acid, uric acid, cholesterol, pyruvic acid, total lipid, and glucose level in experimental mice.